(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the problem of understanding the place of blood and its components as a part of the subject of a criminal offence provided for in Part 4 of Art. 143 of the Criminal Code of Ukraine. The conducted research directly affects both the features of the specified norm and the analysis of relevant provisions of other domestic special legislation. A certain place in the work is given to the understanding of blood and its components in general and specialised reference sources. According to the results of the study, a conclusion was formulated about the urgent need to properly determining the place of blood and its components in the system of legal support for its circulation.